What drives enthusiasm for teaching with digital media? A study of the relative importance of intrinsic value, utility value and self-efficacy using the model averaging approach - Xie, Leilei; Friedrich, Marcus C. G.; Semmler, Luzie; Thies, Barbara (Frontiers in Education, 2025)
Student teachers’ enthusiasm can be understood as the anticipated enjoyment, excitement, and pleasure they experience in their professional activities. However, it is unclear whether enthusiasm for teaching with digital media is identical to general enthusiasm for teaching or to interest in ICT (Information and Communications Technology) and which variables, if applicable, predict it. This cross-sectional online study with N = 143 students shows that enthusiasm for teaching with digital media is a distinct construct from general enthusiasm for teaching and interest in ICT. Multiple regression analysis using model averaging within the information-theoretic approach shows that the most important predictors of enthusiasm for teaching with digital media are perceived utility value of digital media, interest in ICT, teachers’ self-efficacy and self-efficacy regarding media use. Media-related predictors—particularly perceived utility of digital media and interest in ICT—found be to the most influential. Furthermore, perceived utility value of digital media and general teachers’ self-efficacy consistently emerge as the significant predictors with moderate effects across the top five models, which strongly aligns with situated expectancy-value theory. These findings underscore the importance of conceptualizing enthusiasm in a context-specific way and highlight the need to strengthen students’ perceived utility value of digital media in teaching and their self-efficacy for the future teaching profession through diverse practice-oriented learning opportunities to enhance enthusiasm for teaching with digital media.